2014
DOI: 10.4141/cjss2013-064
|View full text |Cite
|
Sign up to set email alerts
|

Changes in amino acids content of humic acids sequentially extracted from peat and sod–Podzolic soil

Abstract: Vialykh, E. A., Ilarionov, S. A., Abdelrahman, H. M. and Vialykh, I. A. 2014. Changes in amino acids content of humic acids sequentially extracted from peat and sod Á Podzolic soil. Can. J. Soil Sci. 94: 575Á583. Amino acids (AA) and peptides are thought to be part of humic acids (HA), but debate whether they are an integral part of the HA is still going. Humic acids sequentially extracted from peat and sod-podzolic soil were analyzed for their AA content, elemental composition and by Fourier transform infrare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…This analysis indicated that HAp fractions differ from HAb fractions by having a higher content of aromatic structures and phenolic (aromatic OH) groups in the HA molecules, as estimated by the A 1610 /A 2920 and A 3400 /A 1610 ratios, respectively ( Figure 1 A,B). A 1610 , A 2920 , and A 3400 are optical densities for aromatic (C=C), aliphatic, and OH groups, respectively [ 42 , 43 ]. A plot of A 1610 /A 2920 versus E4:E6 demonstrated a negative linear correlation (r = −0.66; p < 0.03; n = 18), supporting the conclusion that the low E4:E6 ratio is indeed associated with aromatic components [ 41 ] ( Figure 1 C).…”
Section: Resultsmentioning
confidence: 99%
“…This analysis indicated that HAp fractions differ from HAb fractions by having a higher content of aromatic structures and phenolic (aromatic OH) groups in the HA molecules, as estimated by the A 1610 /A 2920 and A 3400 /A 1610 ratios, respectively ( Figure 1 A,B). A 1610 , A 2920 , and A 3400 are optical densities for aromatic (C=C), aliphatic, and OH groups, respectively [ 42 , 43 ]. A plot of A 1610 /A 2920 versus E4:E6 demonstrated a negative linear correlation (r = −0.66; p < 0.03; n = 18), supporting the conclusion that the low E4:E6 ratio is indeed associated with aromatic components [ 41 ] ( Figure 1 C).…”
Section: Resultsmentioning
confidence: 99%
“…These amino acids were part of the humic substances in the MSWC, SFWC, and the VC. The differences in the total and individual amino acid concentrations can be attributed to variations in the starting feedstock, the biodegradation process employed, the structure of the microbial community, and overall activities of hydrolyzing enzymes [23,24]. According to Fuentes et al [23], the composition of amino acids in compost may range between 4% and 20%.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, Vialykh et al [24] suggested that variations in the composition of amino acids in soils and humic substances were due to the presence of wide range of amino acids in microbial biomass. This can explain the high amino acids content in the VC, that is, 40% greater than the SFWC and 85% greater than the thermophilically produced MSWC (Figure 1).…”
Section: Resultsmentioning
confidence: 99%